2018
DOI: 10.5005/jp-journals-10024-2366
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Rotary and Hand Instrument in removing Gutta-percha and Sealer from Root Canals of Endodontically Treated Teeth

Abstract: ProTaper retreatment files and D-RaCe files are recommended over other instrument systems in terms of quality for managing retreatment root canal cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Patil et al . [ 21 ] in a study reported that rotary instruments are more beneficial than hand instruments for GP retrieval. Due to the frictional heat produced by rotary instruments, which causes the gutta-percha to soften and make it easier to reach the working length, rotary retreatment systems in the current study left less debris in the root canal than manual retreatment systems.…”
Section: Discussionmentioning
confidence: 99%
“…Patil et al . [ 21 ] in a study reported that rotary instruments are more beneficial than hand instruments for GP retrieval. Due to the frictional heat produced by rotary instruments, which causes the gutta-percha to soften and make it easier to reach the working length, rotary retreatment systems in the current study left less debris in the root canal than manual retreatment systems.…”
Section: Discussionmentioning
confidence: 99%
“…The use of nickel-titanium (NiTi) rotary retreatment systems is an efficient and safe approach to remove filling materials during root canal retreatment [ 16 ]. In addition, several dental companies have introduced NiTi rotary retreatment systems on the dental market.…”
Section: Introductionmentioning
confidence: 99%
“…Non-surgical retreatment is the best way to re-establish sound periapical tissues after re-infection or inefficient treatment of a previously obturated teeth due to apical or coronal leakage (1). It requires regaining the accessibility to the root canal system by removing the initial root canal filling, more cleaning, and finally reobturation (2).…”
Section: Introductionmentioning
confidence: 99%